VD_FINDINFO ML / 2014 / 111 vom 3. April 2014 - VD Tribunal cantonal (2014)
MAINLEVÉE DÉFINITIVE, CONDITION DE RECEVABILITÉ, MOTIVATION DE LA DEMANDE | 69 al. 2 ch. 1 LP, 80 LP, 142 al. 3 CPC (CH), 321 CPC (CH)